Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd000530.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Echinacea for preventing and treating the common cold

Abstract: Analysis 1.3. Comparison 1 Echinacea versus placebo to prevent common cold, Outcome 3 Duration: mean difference. Analysis 1.4. Comparison 1 Echinacea versus placebo to prevent common cold, Outcome 4 Total severity score.. . Analysis 1.5. Comparison 1 Echinacea versus placebo to prevent common cold, Outcome 5 Number of patients dropping

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 42 publications
1
78
0
3
Order By: Relevance
“…Previous studies showed to decrease the severity and reduce the duration of colds and upper respiratory infections, especially when Echinacea is taken early in the course of infection (33,34). A recent case-control study showed the favourable effect of Echinacea on gastrointestinal mucosal recovery in children with mucositis due to chemotherapy (35).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed to decrease the severity and reduce the duration of colds and upper respiratory infections, especially when Echinacea is taken early in the course of infection (33,34). A recent case-control study showed the favourable effect of Echinacea on gastrointestinal mucosal recovery in children with mucositis due to chemotherapy (35).…”
Section: Discussionmentioning
confidence: 99%
“…Alprazolam, amiodarone, amlodipine, atorvastatin, bicalutamide, cilostazol, cimetidine, cyclosporine, fluoxetine, fluvoxamine, ginkgo, § isoniazid, nilotinib, oral contraceptives, ranitidine, ranolazine, tipranavir/ritonavir, zileuton Amprenavir, aprepitant, armodafinil, echinacea, § pioglitazone, prednisone, rufinamide 116 Randomized, double-blind, placebo-controlled trials showed no beneficial effects of unrefined echinacea or echinacea capsules on symptoms of common cold or rhinovirus infection compared to placebo. 117,118 Echinacea use has been reported to cause side effects such as nausea, dizziness and gastrointestinal upset.…”
Section: Weak Inducers (20-50% ↓ In Auc)mentioning
confidence: 99%
“…In brief, the numerous randomized studies, systematic reviews and meta-analysis indicate that a likely benefit exists, albeit small, due to the pharmacological activity of Echinacea. [17][18][19] Unfortunately, certain controversy has been generated about these results. As Hart et al 20 discussed regarding the results obtained from three meta-analyses on the efficacy of Echinacea in the prevention and treatment of common cold, the methodology followed in a systematic review (search strategy, inclusion and exclusion criteria, data analysis, etc.)…”
Section: Assessment Of Pfs High and Low Intakesmentioning
confidence: 99%